(untitled) (Research, Society and Development, 2020)
Dentistry has shown a historic evolution marked by different professionalization stages and dental services improvement, culminating in the expansion of the oral health team through the creation of auxiliary categories such as Oral Health Auxiliaries (OHA), Oral Health Technicians (OHT), Dental Prosthesis Auxiliaries (DPA) and Dental Prosthesis Technicians (DPT). Thus, utilizing a data collection documentary research about the professional numbers in each of these categories, this work aims to characterize the distribution national panorama of OHA, DPA, OHT and DPT, in addition to the distribution profile of these professionals concerning the number of Dentists (D). The data show that 205,888 dental auxiliaries are working in Brazil, most of them OHAs and OHTs, which are concentrated in the states of São Paulo, Rio de Janeiro and Minas Gerais. On the other hand, among the Brazilian regions, the Southeast has the highest percentage of professionals in all auxiliary categories in the country. In another perspective, considering the relationships between the total number of Dentists and professionals in each auxiliary category, regional differences between Brazilian states are evident, with values of 1 D/0.42 OHA; 1 D/0.10 OHT; 1 D/0.019 DPA and 1 D/0.069 DPT at the national level. Therefore, it appears that the panorama of professional distribution for the different auxiliary categories in Dentistry is still below the current needs and the data presented here may provide evidence of professional and marketing guidance for these practice areas.